ALTERNATIVE MANAGEMENT OF MARINE TOURISM AREAS AT BANDENGAN WATERS, JEPARA, CENTRAL JAVA - Juliana, .; Zainuri, Muhammad; Sya’rani, Lachmuddin (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2012)
Bandengan waters have the potential to serve as a marine tourism area, its sustainability has to be preserved. Optimal utilization of Bandengan waters can provide benefits not only to the environment but also to the economic improvement of the community. Efforts to optimize marine tourism in Bandengan waters were conducted by reviewing area management alternatives to preserve and improve the welfare of the community. This study aims to analyze the alternative management of the marine tourism area using A'WOT analysis which is a combined analysis of SWOT and AHP (Analytical Hierarchy Process) to establish strategies and to determine alternative management on marine tourism in Bandengan waters. Based on A'WOT analysis obtained alternatives to manage marine tourism area which consists of spatial planning based on biophysical parameters, spatial planning based on the carrying capacity of the environment, increasing public and tourist awareness to cleanliness, improving both the quantity and quality of infrastructure, and the making of legislation. The recommended alternative management is basically aimed to preserve the marine tourism in Bandengan waters and to improve the people's welfare. Keywords: marine tourism, alternative management, SWOT, AHP  Perairan Bandengan memiliki potensi yang dapat dijadikan sebagai kawasan wisata bahari, sehingga perlu dijaga kelestariannya. Pemanfaatan perairan Bandengan secara optimal dapat memberikan manfaat tidak hanya terhadap lingkungan tetapi juga terhadap peningkatan ekonomi masyarakat. Upaya untuk mengoptimalkan wisata bahari di perairan Bandengan dilakukan pengkajian terhadap alternatif pengelolaan kawasan menjaga kelestarian dan meningkatkan kesejahteraan masyarakat. Penelitian ini bertujuan untuk menganalisa alternatif pengelolaan kawasan wisata bahari dengan menggunakan analisa A’WOT yaitu gabungan analisa SWOT dan PHA untuk menetapkan strategi dan menentukan alternatif pengelolaan kawasan wisata bahari di Perairan Bandengan. Berdasarkan analisa A’WOT diperoleh alternatif pengelolaan kawasan wisata bahari yang terdiri dari penataan ruang berdasarkan parameter biofisik, penataan ruang berdasarkan daya dukung lingkungan, peningkatan kesadaran masyarakat dan wisatawan terhadap kebersihan, peningkatan infrastruktur baik kuantitas maupun kualitas, serta pembuatan peraturan perundang-undangan. Alternatif pengelolaan yang dihasilkan pada dasarnya bertujuan untuk menjaga kelestarian kawasan wisata bahari di perairan Bandengan dan meningkatkan  kesejahteraan masyarakat Bandengan. Kata kunci: wisata bahari, alternatif pengelolaan, SWOT, AHP